2005
DOI: 10.4028/www.scientific.net/msf.475-479.4207
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of 316L Stainless Steel in Supercritical Water Environment

Abstract: There is a need to destroy both military and civilian hazardous waste and urgency, mandated by public concern over traditional waste handling methodologies, to safe and efficient alternative technologies. One very effective process for the destruction of such waste is supercritical water oxidation (SCWO). Nevertheless, corrosion of the materials of fabrication is a serious concern. This work intends to obtain the fundamental data for developing the corrosion resistant steel for the construction of SCWO system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1, 2 This is a significant issue because SS316L is used in many applications where structural integrity is crucial, such as marine pipelines and components of ships. 1, 2 Corrosion is expedited not only by water, but when bacteria and marine organisms colonize the surface in a process called biofouling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2 This is a significant issue because SS316L is used in many applications where structural integrity is crucial, such as marine pipelines and components of ships. 1, 2 Corrosion is expedited not only by water, but when bacteria and marine organisms colonize the surface in a process called biofouling.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 This is a significant issue because SS316L is used in many applications where structural integrity is crucial, such as marine pipelines and components of ships. 1, 2 Corrosion is expedited not only by water, but when bacteria and marine organisms colonize the surface in a process called biofouling. 3-6 Previous approaches to limit marine biofouling have consisted of using coatings, including paints, which actively release biocidal toxins such as cuprous oxide, tributyltin, and diuron.…”
Section: Introductionmentioning
confidence: 99%
“…146,147 In studies concerning the corrosion mechanism of stainless steel 316 (SS-316) in SCW oxidation processes, it was shown that duplex layers of oxides were formed and some degree of dealloying was observed. 148,149 Moreover, high corrosion rates were observed on Ni-based alloys and SS-316 when used under SCW oxidation conditions. 150 Watanabe et al found that weight loss in SS-316 was less pronounced than in Ni alloys and showed good resistance in SCW.…”
Section: Main Technological Challengesmentioning
confidence: 99%
“…An overview of the mechanism of corrosion and construction materials including different kinds of steel, ceramics, and Ni-, Ti-, and Zr-based alloys capable of withstanding SCW corrosion in different reactive environments have been reported in the literature . Analysis of corrosion and oxidation rates of ferritic-martensitic steels in SCW processes showed that dissolved oxygen is responsible for the high corrosion rates and that the effect is increased with temperature. , In studies concerning the corrosion mechanism of stainless steel 316 (SS-316) in SCW oxidation processes, it was shown that duplex layers of oxides were formed and some degree of dealloying was observed. , Moreover, high corrosion rates were observed on Ni-based alloys and SS-316 when used under SCW oxidation conditions . Watanabe et al found that weight loss in SS-316 was less pronounced than in Ni alloys and showed good resistance in SCW .…”
Section: Main Technological Challengesmentioning
confidence: 99%
“…Marine corrosion has always been a vital threat to the safe operation of ocean facilities (Belo et al, 1998). 316 L stainless steel (316 L SS), as an economical material (Yoon et al, 2005), is widely used in marine engineering equipment, which relies on the stability of a thin oxide film containing chromium for protecting against corrosion medium such as Cl -. However, in some specific cases, when the steel is covered by marine organisms or crevice forms around it, a local confined environment with high aggressiveness will be generated resulting in the failure of 316 L SS (Marcelin et al, 2015;Marcelin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%